Schools as learning communities for inclusion: insights from case studies of two school clusters in Portugal - Maria José D. Martins; Maria José D. Martins; Amélia Marchão; Amélia Marchão; Teresa Oliveira; Ana Paula Caetano; Luís Tinoca (Frontiers in Education)
IntroductionSchools are facing increasing diversity in student origins due to migrations. The INCLUD-ED approach aims to transform schools into learning communities to increase social cohesion, inclusion, and academic success through successful educational actions like interactive groups, literary gatherings, community participation, dialogical teacher training, and a dialogical model of conflict resolution.MethodsThis research analyzed two school clusters in Portugal implementing the INCLUD-ED approach, focusing on practices and impacts on learning, relationships, and inclusion. A qualitative case study method was used, involving interviews with adults and focus groups with students.ResultsBoth schools promoted literary gatherings and interactive groups. Teacher engagement varied, but most participants agreed the approach increased family/community involvement and enhanced academic and socio-emotional learning.DiscussionThe INCLUD-ED approach appears to transform schools into more inclusive learning communities, though full implementation faces some challenges. Further research is needed to evaluate long-term impacts.